Tentang Pertanggungjawaban Dealer Dalam Perjanjian Jual Beli Sepeda Motor Pada PT. SPS Motor Honda - Ahmad Maulana Rizki; H. Zaenal Arifin Dilaga (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the dealer’s responsibility if there is a hidden defect of the goods claimed by the buyer at PT. SPS Motor Honda. Furthermore, this study aims to analyze the internal and external factors constrain the parties in the motorcycle sale and purchase agreement at PT. The seller and the buyer carried out SPS Motor Honda. This type of research is empirical normative legal research. The results of this study showed that the dealer’s responsible in the case of a hidden defect of the goods claimed by the buyer. The internal and external factors constrain the parties in the motorcycle sale and purchase agreement at PT. SPS Motor Honda. The solutions done by PT. SPS Motor Honda if internal and external factors become obstacles in the motorcycle sale and purchase agreement and a hidden defects that consumers claim, then PT, SPS Motor Honda prioritizes the principle of deliberation/consensus with the aim of customer satisfaction and comfort as well as maintaining the good name of PT. SPS Motor Honda.